Social Studies Learning Model Based on Prince Hidayatullah’s Character Values: Model Pembelajaran Ilmu Sosial Berbasis Nilai-Nilai Karakter Pangeran Hidayatullah - Dini Siti Rahmawati; Sapriya Sapriya; Yeni Kurniawati Sumantri (Academia Open, 2025)
General Background: The rapid advancement of science and technology in Indonesia has led to a decline in socio-cultural values, creating an urgent need for value-based education to preserve national identity. Specific Background: Social Studies (IPS) is a strategic subject for instilling character, yet current practices insufficiently integrate local historical figures. Prince Hidayatullah, a Banjar leader known for religiosity, courage, patriotism, and social care, represents a culturally relevant role model. Knowledge Gap: Previous studies addressed isolated aspects of his legacy without translating them into a structured, classroom-tested pedagogical model. Aims: This study aimed to develop and evaluate a Social Studies learning model based on Prince Hidayatullah’s character values to enhance students’ social care character. Results: Using the ADDIE design and Classroom Action Research cycles, trials in MTs Ats-Tsuur and SMPN 4 Cianjur showed significant improvements in social care scores (N-gain ≈ 0.76, high category) and student engagement. Novelty: The model uniquely integrates ethnopedagogical principles with historical character values into contextual Social Studies instruction. Implications: Findings support the integration of local historical figures into curricula as an effective approach to strengthening student character, fostering cultural identity, and providing adaptable frameworks for value-based learning across diverse educational contexts.Highlight : Developing a social studies learning model based on the values of Prince Hidayatullah's struggle. Strengthening students' social awareness through contextual learning. Proven effective in improving students' understanding and character behavior. Keywords : Social Studies Learning Model, Character Values, Pangeran Hidayatullah, Character Education, Contextual Learning